PEMBELAJARAN SASTRA DAN IMPLIKASINYA TERHADAP PENDIDIKAN KARAKTER SISWA - Liza Wiwita (Universitas Negeri Medan, 2019)
Abstract This study discusses literary learning and its implications for student character education. This study aims to explain and describe (1) The role of literature in character education. (2) Implementation of character education through literary learning. The data in this study the researchers obtained through literature studies and from other sources that support. The conclusion in this study is that literature is very instrumental in the character education of students (humans), namely in language development, cognitive development, personality development, and social development. Second, literature as a cathartic media in literary learning can be used receptively (accepting) and expressive (the ability to express) in character education. Third, literary works that present various themes can be used as a medium for students (humans) to recognize and understand the quality of their own character or character. . Fourth, literary works that narrate and describe various types of character characters, can be used as a medium for character education for students (humans), which is to set an example of the quality of character or personality levels of characters that must be emulated. Through literary learning, students are expected to grow into mature human beings who are cultured, independent, able to express themselves with their thoughts and feelings well, broad-minded, critical, characterized, refined in character, and polite. Therefore, literary learning must be encouraged.Keywords: Literary Learning, Character Education